Effects of leaf domatia on intraguild interactions between Amblyseius swirskii and Phytoseiulus persimilis (Acari: Phytoseiidae) - Narges Abbasi-Teshnizi; Azadeh Zahedi Golpayegani; Alireza Saboori (Persian Journal of Acarology)
Leaf domatia as a habitat-produced structure is considered to moderate the interaction intensity among guild parties. We studied whether domatia of sweet pepper (Capsicum annum) leaves could reduce the adverse effects of predation of a phytoseiid on behalf of an intraguild predatory mite on a phytoseiid intraguild prey, and a tetranychid extraguild prey. In the domatia-provided treatments where Amblyseius swirskii (Athias-Henriot) females were considered as predator, significantly fewer Phytoseiulus persimilis Athias-Henriot juveniles were killed, and eaten in comparison with the treatments without domatia. The predation rate of A. swirskii was affected by the domatia i.e. the number of eaten P. persimilis was significantly lower on patches with four domatia rather than those with no domatium, however, no significant difference was observed between those in patches with two, and four domatia. Both natural, and artificial domatia could reduce the predation rate on P. persimilis juveniles. When P. persimilis females were considered as predators, the number of A. swirskii killed juveniles was affected neither by presence nor by the number of leaf domatia. The number of eaten Tetranychus urticae Koch eggs/larvae in patches with either of the intraguild predator species was not affected by the presence, the number, and the type of domatia. We suggest that leaf domatia could affect the survival of phytoseiid predatory mites as the guild participants even when the highly aggressive intraguild predator, A. swirskii, enters such structures.